Modelling the complexity of the coaching process - Cushion, C. (International Journal of Sports Science and Coaching, 2007)
An examination of the considerable landscape of coaching research reveals a range of theoretical and empirical perspectives and insights into coaching. Despite this, an in-depth understanding of the coaching process appears to remain lacking and we seem as far removed from a consensus about the nature of coaching as ever. Consequently, coach development and coaching practice in North America and the UK operates without reference to any guideline or models for good practice that practitioners undoubtedly crave. It would appear that "a model of coaching is required that has at its heart sound theoretical and research foundations, which are applicable to all sports, coaches and age groups" . If this is the case, and given the scale of current coaching research activity; why have coaching scholars been unable to develop such a model thus far? Perhaps coaching is an enterprise where a definitive set of concepts and principles will always be elusive and as such a singular all encompassing model may not be possible. Alternatively, if it were possible, would such an approach be in the best interests of developing coaching's conceptual base? The aim of this paper is to build upon earlier work and explore some of the issues surrounding the generation of and outcomes from a coaching process model. This includes a model for coaching (idealistic representation) and a model of coaching (based on empirical research).